GIS-based Point and Non-point Sources of Pollution Identification in Cameron Highlands - Malakahmad, Dr, Amirhossein, Dr; Eisakhani, Mahdieh; Kutty, S.R.M. (Universiti Teknologi MARA, 2008)
Almost 90% of the water supply for Peninsular Malaysia is derived from the highlands. An estimated 5.8 million liters a day is extracted for drinking water supply at several intake points along rivers originating from the mountainous forests of Cameron Highlands. However, in the last decade the rivers in Cameron Highlands have become polluted resulting in widespread environmental problems in the area. In this study, point sources (PSs) and non-point sources (NPSs) pollution in Cameron Highlands were identified and compiled using a Geographical Information System (GIS), a powerful modeling tool. This would be useful in providing the necessary knowledge in making management decisions. Land use classifications, pollutant concentrations and rainfall database were generated for the region to determine the major PSs and NPSs. The results from the study indicated that agricultural activities contributed to most of the eroded soils in Cameron Highlands followed by urbanization and infrastructures activities. Sewage from commercial activities was found to be the greatest PS pollution in the study area. In addition, it was found that some of the PSs and NPSs in Cameron Highlands have very high BOD and exceeding any effluent discharge standards of the Environmental Quality Act 1974 (EQA 1974).